Central limit theorems for functionals of large sample covariance matrix and mean vector in matrix-variate location mixture of normal distributions - Taras Bodnar; Stepan Mazur; Nestor Parolya (Örebro University School of Business, 2017)
In this paper we consider the asymptotic distributions of functionals of the sample covariance matrix and the sample mean vector obtained under the assumption that the matrix of observations has a matrix-variate location mixture of normal distributions. The central limit theorem is derived for the product of the sample covariance matrix and the sample mean vector. Moreover, we consider the product of the inverse sample covariance matrix and the mean vector for which the central limit theorem is established as well. All results are obtained under the large-dimensional asymptotic regime where the dimension p and the sample size n approach to in nity such that p=n ! c 2 [0;+1) when the sample covariance matrix does not need to be invertible and p=n ! c 2 [0; 1) otherwise.
Keywords: C00; C13; C15; 330; Normal mixtures; skew normal distribution; large dimensional asymptotics; stochastic representation; random matrix theory